PENGUATAN PARTISIPASI PEMILIH DALAM MENGHADAPI PEMILU SERENTAK TAHUN 2024 DI PROVINSI SULAWESI TENGAH - Awaluddin, Awaluddin; Dewi Primayanti , Andi; Danduru Salurante, Belona (Maleo Law Journal, 2022)
Participation literally means participation. in a political context this refers to citizens' participation in various political processes. Political participation can also be understood as the process of citizen involvement in all stages of policy, from decision making to decision evaluation, including the opportunity to participate in the implementation of decisions. Widespread political participation is a hallmark of political modernization. The term political participation has been used in various meanings related to behavior, attitudes and perceptions which are an absolute requirement for political participation. Huntington and Nelson have written it in their book No Easy Choice: Political Participation in Developing Countries which is interpreted as â€œBy political participation we mean activity by private citizens designed to influence government decision making. Participation may be individual or collevtive , organized or spontaneous , sustained or sporadic , peaceful or violent , legal or illegal , effective or ineffectiveâ€. From the above definition we can conclude that political participation is the activity of citizens acting as individuals, which are intended to influence decision-making by the government. Furthermore, from the above definition it can also be concluded that participation can be individual or collective, organized or spontaneous, continuous or sporadic, peaceful or violent, legal or illegal, effective or ineffective.